2012
DOI: 10.1159/000345525
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of JNK, ERK1/2, and p38 Mitogen-Activated Protein Kinases on Endothelial Cell Tissue Repair Functions in Response to Tumor Necrosis Factor-α

Abstract: Tumor necrosis factor (TNF)-α can alter tissue repair functions in a variety of cells including endothelial cells. However, the mechanism by which TNF-α mediates these functional changes has not fully been studied. We investigated the role of mitogen-activated protein kinases (MAPKs) on mediating the regulatory effect of TNF-α on the tissue repair functions of human pulmonary artery endothelial cells (HPAECs). TNF-α protected HPAECs from undergoing apoptosis induced by serum and growth factor deprivation, augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
3
9
0
Order By: Relevance
“…Experimental data obtained from transmembrane migration assays revealed that AV-38/398 suppresses migration of endothelial cells in a dose-dependent manner. Western blotting experiments clearly showed a decrease in the activation state integrin-linked signaling pathways involved in cell migration and proliferation, such as FAK, Akt, and ERK1/2 [30,34]. Our results partially overlap with those reported for cilengitide in HUVECs [14].…”
Section: Discussionsupporting
confidence: 86%
“…Experimental data obtained from transmembrane migration assays revealed that AV-38/398 suppresses migration of endothelial cells in a dose-dependent manner. Western blotting experiments clearly showed a decrease in the activation state integrin-linked signaling pathways involved in cell migration and proliferation, such as FAK, Akt, and ERK1/2 [30,34]. Our results partially overlap with those reported for cilengitide in HUVECs [14].…”
Section: Discussionsupporting
confidence: 86%
“…26 We show that in TNFα-stimulated ECs, 6-MP decreases the amount of JNK phosphorylation (p-JNK) and thus reduces JNK activation ( Figure 3A and 3B). A similar reduction in p-JNK was also observed when a Rac1 inhibitor was used, suggesting that indeed inactivation of Rac1 by 6-MP could be responsible for reduced levels of p-JNK.…”
Section: -Mp Inhibits Rac1 Activation and Rac1-mediated Signalingmentioning
confidence: 71%
“…A wide variety of stimuli such as oxidative stress can induce apoptosis of endothelial cells and endothelial dysfunction, which may be regulated by different signal pathways (Maruyama et al 2012;Qin et al 2015). Mitogen-activated protein kinases (MAPKs), including extracellular signalregulated kinase 1/2 (ERK1/2), c-Jun NH2-terminal kinase (JNK), and p38, are a family of central signaling molecules that respond to numerous stimuli and are known to participate in cell survival and death decisions (Hardie 2011;Kanaji et al 2013). Moreover, the activation of JNK and p38 MAPK phosphorylation can induce apoptotic responses in endothelial cells (Yoshizuka et al 2012).…”
Section: Introductionmentioning
confidence: 99%